SOME POSSIBILITIES OF OPTOACOUSTIC CONTROL OF METAL WARE - A. R. Bayev; V. G. Gudelev; A. I. Mitjkovets; M. V. Asadchaya (Литьë и металлургия, 2012)
Possibilities of use of optoacoustic contact method for control of metalware are analysed and results of experimental surveys on identification of superficial cracks of micron opening by moving beam of pulse and laser emission are presented.